Jonathan Edwards and the Bible - Brown, Robert E., 1958- (Indiana University Press, 2002)
This study is the first of its kind to examine critical biblical interpretation in early American history. Focusing on Jonathan Edwards's biblical writings, it suggests that Edwards's biblical interpretation is the key to understanding his broader engagement with critical methods and provides a unifying thread within his theological work. Very few students of American religious history are aware of the vast quantity of Edwards's biblical writings, let alone his engagement with critical historical thought. The rage of British society in the middle of the 17th century, particularly as it related to church-state issues, biblical criticism has been considered a late 19th-century phenomenon in American religious history. It was at that time that it emerged and rapidly grew as a technical discipline in American theological schools. However, as Robert E. Brown shows in this path-breaking study, far from being a 'modern' preoccupation, the relationship of the Bible to critical thought is almost as old as the American experience itself. Brown's study of Edwards's biblical writings shows him to have been one of the most thoroughly engaged thinkers regarding critical problems in the colonial period. The impact of this revolution in biblical interpretation can be traced to nearly every area of Edwards's intellectual career - epistemology, historiography, natural theology, typology, natural science, comparative religion, constructive theology, and public discourse. This engagement resulted in a subtle but distinct transformation of Edwards's understanding of the biblical narratives and their relation to the new scientific modes of inquiry, a transformation that anticipated similar developments in 19th-century American religious thought.